Photosynthetic Trichomes Contain a Specific Rubisco with a Modified pH-Dependent Activity. Issue 4 (1st March 2017) - Laterre, Raphaëlle; Pottier, Mathieu; Remacle, Claire; Boutry, Marc
Abstract : Secretory cells contain a specific Rubisco, the small subunit of which belongs to a so-far-uncharacterized phylogenetic cluster and confers a modified pH-dependent activity. Abstract: Ribulose-1, 5-biphosphate carboxylase/oxygenase (Rubisco) is the most abundant enzyme in plants and is responsible for CO2 fixation during photosynthesis. This enzyme is assembled from eight large subunits (RbcL) encoded by a single chloroplast gene and eight small subunits (RbcS) encoded by a nuclear gene family. Rubisco is primarily found in the chloroplasts of mesophyll (C3 plants), bundle-sheath (C4 plants), and guard cells. In certain species, photosynthesis also takes place in the secretory cells of glandular trichomes, which are epidermal outgrowths (hairs) involved in the secretion of specialized metabolites. However, photosynthesis and, in particular, Rubisco have not been characterized in trichomes. Here, we show that tobacco ( Nicotiana tabacum ) trichomes contain a specific Rubisco small subunit, NtRbcS-T, which belongs to an uncharacterized phylogenetic cluster (T). This cluster contains RbcS from at least 33 species, including monocots, many of which are known to possess glandular trichomes. Cluster T is distinct from the cluster M, which includes the abundant, functionally characterized RbcS isoforms expressed in mesophyll or bundle-sheath cells. Expression of NtRbcS-T in Chlamydomonas reinhardtii and purification of the full Rubisco complex showed that this isoform conferred higher V  max and K  m values as well as higher acidic pH-dependent activity than NtRbcS-M, an isoform expressed in the mesophyll. This observation was confirmed with trichome extracts. These data show that an ancient divergence allowed for the emergence of a so-far-uncharacterized RbcS cluster. We propose that secretory trichomes have a particular Rubisco uniquely adapted to secretory cells where CO2 is released by the active specialized metabolism.